La tenencia de vivienda propia desde una perspectiva de género - Rubio , Jeniffer (2018)
This document seeks to understand the complex social reality of housing tenure,by identifying determinants that influence the likelihood that households will havetheir own house. As well as establishing the relationship between the probability ofhouseowner headed by women in contrast to men, in order to establish this differenceas a starting point to implement policies aimed at guaranteeing the rights of thepopulation. A probit model with microdata from the Survey of Living Conditions(2013-2014) of the INEC is calculated. As a main finding, in Ecuador there is a lowerprobability to have their own house in the case of households headed by women inrelation to men. In addition, there are other factors that influence such probability,such as consumption (proxy of income ), age, level of education, region of residence,and employment status of the head of household. Additionally, the importance ofaccess to some type of financing on the probability of owning a home is observed. Theresults allow to work more in the achievement of programs and policies to increasethe rates of housing tenure, focused mainly on households with fewer resources andfemale heads of household.